Regulatory focus and adherence to self-care behaviors among adults with type 2 diabetes. Issue 6 (17th August 2016) - Avraham, Rinat; Van Dijk, Dina; Simon-Tuval, Tzahit
Abstract: The aims of this study were, first, to test the association between regulatory focus of adults with type 2 diabetes and their adherence to two types of self-care behaviors – lifestyle change (e.g. physical activity and diet) and medical care regimens (blood-glucose monitoring, foot care and medication usage). Second, to explore whether a fit between the message framing and patients' regulatory focus would improve their intentions to adhere specifically when the type of behavior fits the patients' regulatory focus as well. A cross-sectional study was conducted among 130 adults with type 2 diabetes who were hospitalized in an academic medical center. The patients completed a set of questionnaires that included their diabetes self-care activities, regulatory focus, self-esteem and demographic, socioeconomic and clinical data. In addition, participants were exposed to either a gain-framed or a loss-framed message, and were then asked to indicate their intention to improve adherence to self-care behaviors. A multivariable linear regression model revealed that promoters reported higher adherence to lifestyle change behaviors than preventers did ( B = .60, p = .028). However, no effect of regulatory focus on adherence to medical care regimens was found ( B = .46, p = .114). In addition, preventers reported higher intentions to adhere to medical care behaviors when the message framing was congruent with prevention focus ( B = 1.16, p = .023). However, promoters did not report higher intentions to adhere to lifestyle behaviors when the message framing was congruent with promotion focus ( B = −.16, p = .765). These findings justify the need to develop tailor-made interventions that are adjusted to both patients' regulatory focus and type of health behavior.